Systematic multi‐level analysis of an organelle proteome reveals new peroxisomal functions. Issue 9 (27th September 2022) - Yifrach, Eden; Holbrook‐Smith, Duncan; Bürgi, Jérôme; Othman, Alaa; Eisenstein, Miriam; van Roermund, Carlo WT; Visser, Wouter; Tirosh, Asa; Rudowitz, Markus; Bibi, Chen; Galor, Shahar; Weill, Uri; et al.
Abstract: Seventy years following the discovery of peroxisomes, their complete proteome, the peroxi‐ome, remains undefined. Uncovering the peroxi‐ome is crucial for understanding peroxisomal activities and cellular metabolism. We used high‐content microscopy to uncover peroxisomal proteins in the model eukaryote – Saccharomyces cerevisiae . This strategy enabled us to expand the known peroxi‐ome by 40% and paved the way for performing systematic, whole‐organellar proteome assays. By characterizing the sub‐organellar localization and protein targeting dependencies into the organelle, we unveiled non‐canonical targeting routes. Metabolomic analysis of the peroxi‐ome revealed the role of several newly identified resident enzymes. Importantly, we found a regulatory role of peroxisomes during gluconeogenesis, which is fundamental for understanding cellular metabolism. With the current recognition that peroxisomes play a crucial part in organismal physiology, our approach lays the foundation for deep characterization of peroxisome function in health and disease. Synopsis: High‐content imaging analysis uncovers the peroxisomal proteome of Saccharomyces cerevisiae . Systematic, whole‐organellar proteome assays reveal new players in peroxisome organization, targeting, and function. Targeting dependency assays unveiled non‐canonical targeting routes of Pex5‐dependent cargo proteins. Metabolomic analysis of each peroxisomal mutant revealed the role of several newly‐identified resident enzymes. Targeted inspection of two newly identified peroxisomal proteins uncovered a regulatory role of peroxisomes during gluconeogenesis. Abstract : High‐content imaging analysis uncovers the peroxisomal proteome of Saccharomyces cerevisiae . Systematic, whole‐organellar proteome assays reveal new players in peroxisome organization, targeting, and function.